Evaluation of hydrodynamic behavior of the perforated gas distributor of industrial gas phase polymerization reactor using CFD-PBM coupled model. (2nd November 2015) - Akbari, Vahid; Nejad Ghaffar Borhani, Tohid; Aramesh, Roya; Hamid, Mohd. Kamaruddin Abd.; Shamiri, Ahmad; Hussain, Mohamed Azlan
Highlights: Effect of perforated plate distributor was studied in practical gas phase fluidized bed reactor. A CFD-PBM/DQMOM coupled model was implemented. In sensitivity analysis, the drag coefficient has significant effect on fluidization structure. In perforated case, the fluidization structure is more heterogeneous than complete sparger. Perforated distributor was predicted dead zone formation near the corners of distributor. Abstract: A 2D computational fluid dynamics (Eulerian–Eulerian) multiphase flow model coupled with a population balance model (CFD-PBM) was implemented to investigate the fluidization structure in terms of entrance region in an industrial-scale gas phase fluidized bed reactor. The simulation results were compared with the industrial data, and good agreement was observed. Two cases including perforated distributor and complete sparger were applied to examine the flow structure through the bed. The parametric sensitivity analysis of time step, number of node, drag coefficient, and specularity coefficient was carried out. It was found that the results were more sensitive to the drag model. The results showed that the entrance configuration has significant effect on the flow structure. While the dead zones are created in both corners of the distributors, the perforated distributor generates more startup bubbles, heterogeneous flow field, and better gas–solid interaction above the entrance region due to jet formation.